The Role of Social Studies Education in Navigating Globalization and National Dynamics: Challenges and Opportunities in the 21st Century - Susanti, Rahma (Jurnal Studi Sosial / Journal of Social Studies, 2025)
This research examines the evolving role of social studies education in the context of globalization and changing national dynamics. Using a qualitative literature review methodology, this study analyzes current research, educational policies, and case studies related to social studies education in the globalized world. The findings reveal that social studies education plays a crucial role in developing students' global competencies while simultaneously strengthening their national identity. Key challenges identified include integrating technology effectively, addressing complex global issues, and balancing global and local perspectives. However, significant opportunities exist through innovative pedagogical approaches, project-based learning, and the development of 21st century skills. The study concludes that a reformed approach to social studies education-one that embraces both global citizenship values and national cultural perspectives-is essential for preparing students to thrive in an increasingly interconnected world while remaining grounded in their cultural heritage. This research contributes to the ongoing discourse on educational adaptation in response to global challenges and provides practical implications for curriculum development, teacher preparation, and educational policy in the field of social studies